The Synergy between literature in English and Language Learning in Higher Education: Review of Literature in practice - Gabriel, Bazimaziki (International Journal of Humanities and Education Development (IJHED), 2020)
The interface between literature and language is a topic explored in this essay by looking at language as a tool of communication and literature as a tool to enrich language skills. Literature is concerned with artistic use of language to depict the socio- cultural, political and economic situations of human beings in the world they live. In higher education, literature in English is taught not only to equip learners with ethical values, critical thinking and analytical skills but also communication skills in English. In this paper, theories of using literature in language learning are reviewed with specific interest in English as an international language. The paper anchored on two of Lazar’s approaches such as language - based approach to using literature in language learning on the one hand, and literature as a tool for personal enrichment on the other hand. Discussion reveals that literature is an indispensable tool to enrich language knowledge and proficiency if well utilized. Teachers of Literature should consider that it is a means to enrich the acquirer’s language knowledge and proficiency.